Glass powder for conductive gold paste as well as preparation method and application of glass powder
By using the composite technology of composite glass powder and gold powder, the problems of unevenness and poor density during the sintering of conductive gold paste are solved, the adhesion strength between the ceramic substrate and the gold film is improved, and the preparation of high-performance conductive gold paste is realized. Meets the manufacturing needs of high-frequency and high-strength electronic components.
Patent Information
- Application Number
- CN202411281576.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-17
AI Technical Summary
The existing conductive gold paste is prone to problems such as unevenness, poor density and low binding force during the sintering process, and copper powder is prone to oxidation, resulting in a decrease in conductivity, making it difficult to meet the needs of high-frequency and high-strength electronic components manufacturing.
The composite glass powder is adopted, including P2O5-SiO2-B2O3-Al2O3 and Bi2O3-SiO2-B2O3-Al2O3 systems, by adding CuO, Sb2O3, Na2O, CaO and other components, the chemical stability and crack resistance of the glass powder are improved, and the chemical stability and crack resistance of the glass powder are improved with The gold powder is compounded to form a high-performance gold paste, which is used to prepare conductive gold paste.
It realizes high adhesion, conductivity and corrosion resistance of conductive gold paste, reduces cracks and peeling phenomena of sintered film, improves the adhesion strength between ceramic substrate and gold film, and satisfies lead-free, non-toxic and highly reliable sexual needs.
Smart Images

Figure BDA0005041788690000071 
Figure HDA0005041788710000011 
Figure HDA0005041788710000012
Abstract
Description
Technical Field
[0001] The invention belongs to the field of electronic packaging, and in particular relates to glass powder for conductive gold paste, a preparation method and application thereof. Background Art
[0002] In recent years, with the continuous improvement of my country's integrated technology level, electronic packaging technology has developed towards high frequency, high speed, high strength, miniaturization and high integration. The performance requirements for materials are also getting higher and higher, and the demand is growing year by year.
[0003] Although copper paste technology has been partially adopted to replace silver paste and gold paste to reduce costs, copper powder is easily exposed to water and oxygen in the air, causing oxidation reactions and resulting in decreased conductivity. Compared with copper powder, gold powder has good chemical stability, is not easily oxidized in the air, has good conductivity, and has a simple and uncomplicated preparation process. When used in the preparation of electronic paste, all properties are relatively stable. Sintered gold paste is widely used in the manufacture of electronic components such as capacitors, ceramic substrate electrodes, and high-end components such as high-voltage and high-frequency ceramic parts due to its excellent conductivity, solderability, and corrosion resistance. With the rapid development of the electronics industry, the requirements for the reliability of electronic components and the printing accuracy of pastes are getting higher and higher. The current conductive gold paste is prone to problems such as uneven sintered film, poor density, and low bonding strength.
[0004] To solve the above problems, patent applications CN115424762A and CN113506648A disclose a glass CaO-B2O3-SiO2 system specially made for the characteristics of LTCC A6 thin strip from the perspectives of slurry and gold powder modification, solving the substrate reliability problem caused by the unstable sintering quality of the gold inner layer conductor slurry. Patent application CN117342797A discloses a glass formula (B2O3-Bi2O3-CuO system) for NTC thermistor gold electrode glass powder, which reduces the melting point of gold electrode slurry and improves the stability of gold electrode slurry and the compatibility of NTC ceramic materials in a targeted manner. Starting from additives, CN108053915A replaces conventional inorganic copper in the form of organic copper, which improves the dispersion of slurry and the bonding performance of gold wire. JP10340619A prepares a low-temperature co-fired gold paste by mixing and dispersing gold particles with a particle size of 1.0 μm and glass material (PbO-B2O3-SiO2) with a softening point of less than 450°C with an organic carrier. EP1560227A1 uses lead-free Bi-based glass to prepare a low-temperature sintered high-conductivity gold paste. However, the patent describes the bonding strength of glass powder to the paste and the substrate. JP2893711B2 adds lead compounds and glass powder (Al2O3-PbO-SiO2-B2O3-CaO) to the gold paste to promote the formation of a strong reaction intermediate at the interface between the conductor and the ceramic substrate during the slurry sintering, forming a conductor without defects such as peeling and cracks, and at the same time can improve the bonding strength between the conductor and the ceramic substrate. CN114835404B, which is close to this patent, provides glass powder for copper paste (B2O3-SiO2-ZnO-BaO-Al2O3 system). The glass powder has good wettability with the MLCC ceramic matrix, strong adhesion, and stable chemical properties. Inspired by the above patents and combined with the development needs of lead-free and high reliability, this patent uses different glass systems for compounding to design a high-performance and high-stability gold paste to meet the development needs of lead-free, conductors without defects such as peeling and cracks, and high bonding strength between conductors and ceramic substrates.
[0005] The glass powder designed by the present invention has high mechanical strength, good resistance to electroplating solution, good thermal expansion matching with ceramic substrate and gold powder, excellent wettability, lead-free and non-toxic, and has obvious sintering effect on gold paste. It improves the adhesion, conductivity and corrosion resistance of conductive gold paste. Summary of the invention
[0006] The purpose of the present invention is to solve the problems existing in the prior art and to provide a glass powder for gold paste, a preparation method and an application thereof.
[0007] To achieve the above object, the technical solution adopted by the present invention is as follows:
[0008] In the first aspect, the present invention provides a composite glass powder for gold paste, the composite glass powder includes glass powder A and glass B; the glass powder A system is P2O5-SiO2-B2O3-Al2O3, P2O5 and ZrO2 increase the network skeleton of the glass, improve the chemical stability and crack resistance of the glass powder, CuO and Sb2O3 reduce the surface tension and improve the bonding strength of the substrate, and Na2O and CaO are introduced to reduce the melting temperature and softening temperature. Glass powder system B is Bi2O3-SiO2-B2O3-Al2O3, Bi2O3 is the main network former of lead-free and low-melting-point glass, and when mixed with glass powder A, it can promote low-temperature and high-densification sintering of gold paste;
[0009] As a preferred technical solution of the present invention: the glass powder A, measured by molar percentage, comprises the following components: 5.0-10.0% P2O5, 20.0-25.0% SiO2, 25.0-35.0% B2O3, 3.0-10.0% Al2O3, 15-20.0% ZnO, 5.0-10.0% Na2O, 0-10.0% NaF, 2-7.0% CaO, 0-5.0% M (M=CuO, Sb2O3 or ZrO2), wherein the sum of the contents of CuO, Sb2O3 and ZrO2 in the glass is greater than 3%, and the sum of the contents of Na2O and CaO is greater than 10%. Glass powder B includes the following components calculated by molar percentage: 15.0-20.0% Bi2O3, 40.0-50.0% SiO2, 15-20.0% B2O3, 10.0-15.0% Al2O3, 0-10% K2O, 0-5.0% CuO. The sum of the content of CuO and K2O in glass is greater than 4%. Glass within this element range has good glass-forming properties, good sintering activity, good acid resistance and good adhesion to the substrate. The ratio of glass powder A to glass powder B is preferably 2:1;
[0010] The glass powder can be prepared by any production method such as a sol-gel method, a spray pyrolysis method, an atomization method, etc., in addition to the usual method of mixing, melting, rapidly cooling, and pulverizing the raw material compounds of the respective components.
[0011] Gold powder, as the functional phase of conductive paste, has excellent conductivity and chemical stability. It is currently widely used in pastes for integrated circuits and electronic components. A large number of comparative studies on gold powders have found that gold powders with smaller particle sizes have higher sintering activity and lower bulk density. They shrink severely after sintering, but can achieve low-temperature densification sintering. Copper powders with larger particle sizes have higher bulk density and higher sintering temperature, and will not cause electrode cracking after sintering. By compounding spherical gold powder A with D50=1~5μm and quasi-spherical gold powder B with D50=7~10μm, dense sintering of the electrode can be achieved when the mass ratio of gold powder A to gold powder B is in the range of 1~3;
[0012] As a preferred technical solution of the present invention: the gold powder is spherical gold powder with D50=1μm and D50=8μm. When the mass ratio is within the range of 1 to 2, a dense electrode layer can be obtained;
[0013] The present invention also provides an application of the glass powder as described in any one of the above items, wherein the glass powder is used as a sintering aid and a binder to prepare a conductive gold paste.
[0014] In the application described above, the components and contents of the conductive paste are: 80-85% gold powder, 3-7% glass powder, and 10%-15% organic carrier.
[0015] In the application described above, the organic carrier is composed of 15-20wt% of resin and the balance of organic solvent; the resin is ethyl cellulose or acrylic resin; and the organic solvent is pinene alcohol, diethylene glycol butyl ether or diethylene glycol butyl ether acetate.
[0016] As a preferred embodiment of the present invention, the organic carrier comprises 75.0-85.0% of solvent and 15.0-25.0% of resin by mass percentage. The preferred solvent comprises one or more of diethylene glycol butyl ether acetate, diethylene glycol butyl ether, and terpineol, and the preferred resin is ethyl cellulose.
[0017] The present invention also discloses a method for preparing a conductive gold paste, comprising the following steps:
[0018] S1. Weigh the solvent and the resin, dissolve the resin uniformly in the solvent at 80-90° C., and stir thoroughly to form a uniform organic carrier.
[0019] S2, the organic carrier, glass powder A, glass powder B, gold powder A and gold powder B prepared in step S21 are weighed in proportion and stirred to form a slurry. The slurry is then fully ground with a three-roll mill to finally prepare a gold paste that meets the performance requirements.
[0020] Furthermore, in step S2, the preparation of the glass powder includes the following steps:
[0021] S21. Weigh glass raw materials, mix and grind them thoroughly, put them into a platinum crucible, and melt them at 1300° C. for 60 minutes. Then pour the molten glass into deionized water for quenching, so that the glass is broken into particles.
[0022] S22, ball-milling the glass powder prepared in step S21 for 2 hours through a ball-milling process, and reducing the particle size D50 of the glass powder after ball-milling to 2-3 μm.
[0023] As in the application described above, the conductive paste is also printed on the surface of the aluminum oxide or aluminum nitride substrate, and then dried and co-fired in sequence to obtain a gold electrode.
[0024] For the application as described above, the drying temperature is 120-150°C and the time is 10-20min; the sintering process is: first, in an air atmosphere, the temperature is increased to 600°C at a heating rate of 10-15°C / min and then kept warm for 30-60mins, and then in an air atmosphere, the temperature is increased to 800-900°C at a heating rate of 10-15°C / min and then kept warm for 2-3h.
[0025] In the application described above, the printed electrode is composed of a gold film and a substrate. The gold film has no warping or cracking, the average square resistance of the gold film is 5-15.3 mΩ / square, and the tension between the gold film and the substrate is 10-25N.
[0026] Beneficial effects of the invention: The invention provides a composite glass powder and successfully applies it to aluminum oxide and aluminum nitride gold paste. Under the sintering system, the elements in the glass generate a bonding layer with a micro-nano structure on the surface of the substrate to improve the interface fracture toughness. This method reduces the changes in electrical properties and thermal stress caused by the mutual reaction between glass and ceramics. The bonding layer with a micro-nano structure can achieve high-strength bonding between the electrode and the ceramic body.
[0027] The glass powder prepared by the present invention reduces the surface tension, adjusts the thermal expansion coefficient of the glass, enhances the wettability between the glass and the copper powder, improves the bonding force of the substrate, and makes the glass powder have a good sintering effect by adding CuO and Sb2O3 to the phosphorus borosilicate glass system. The introduction of NaF promotes P to form a stable network structure in the glass, and the introduction of Na2O and CaO reduces the melting temperature and softening temperature. The glass powder system B is Bi2O3-SiO2-B2O3-Al2O3. Bi2O3 is the main network former of the lead-free and low-melting-point glass. It is mixed with the glass powder A to improve the chemical stability and thermal stability of the glass, and achieve the purpose of sintering densification of the gold electrode, low porosity, and good conductivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 Acid and alkali resistance weight loss of glass powder A, glass powder B, and composite glass powder in Examples 1 to 4
[0030] Figure 2 (a) to (d) SEM images of the conductive gold thick film and substrate cross section of Examples 1 to 4, respectively DETAILED DESCRIPTION
[0032] In order to more clearly illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments. The described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, other embodiments obtained by ordinary technicians in the field without making creative work all belong to the scope of protection of this application.
[0033] The present invention is described below in conjunction with specific embodiments.
[0034] Example 1
[0035] A gold paste for an aluminum oxide / aluminum nitride substrate comprises the following components in percentage by weight:
[0036] 80wt% gold powder, 7wt% composite glass powder, and 13wt% organic carrier.
[0037] The organic carrier in this embodiment includes the following components in weight percentage: 70% of diethylene glycol butyl ether acetate, 15% of terpineol, and 15% of ethyl cellulose.
[0038] The gold powder in this embodiment includes spherical gold powder with D50=1 μm and D50=8 μm, and the mass ratio of the two is 1:1.5.
[0039] The glass powder A and glass powder B in the composite glass powder of this embodiment are 2:1, and the glass powder A includes the following components in weight percentage: 5.0% P2O5, 20.0% SiO2, 35.0% B2O3, 4.0% Al2O3, 16.0% ZnO, 8.0% Na2O, 5.0% NaF, 3.0% CaO, 2.0% CuO, 1.0% ZrO2, 1.0% Sb2O3. The glass powder B includes the following components in weight percentage: 15.0% Bi2O3, 50.0% SiO2, 15.0% B2O3, 12.0% Al2O3, 5.0% K2O, 2.0% CuO.
[0040] The preparation method of the gold paste described in this embodiment comprises the following steps:
[0041] S1. Weigh the solvent and the resin, dissolve the resin uniformly in the solvent at 80-90° C., and form a uniform organic carrier by fully stirring.
[0042] S2, weigh glass powder A, glass powder B, gold powder and the organic carrier prepared in step S1 according to proportion and stir them evenly to form a slurry. Then use a three-roll mill to fully grind the slurry to finally prepare a gold slurry that meets the performance requirements.
[0043] The method for preparing the glass described in this embodiment comprises the following steps:
[0044] S1. Weigh the glass raw materials, mix and grind them thoroughly, and put them into a platinum crucible. Melt them at 1300℃ for 60mins.
[0045] S2. Pour the molten glass into deionized water for quenching, and crush the molten glass with a ball mill to reduce the particle size D50 of the particles to 2-3 μm, thereby obtaining the glass powder.
[0046] The use and testing method of the gold paste described in this embodiment
[0047] The prepared gold paste was printed on an alumina / aluminum nitride substrate by screen printing to a thickness of 40 μm. The paste was dried for 0.5 h in an oxygen environment at 130°C. The paste was then sintered in an air atmosphere at a heating rate of 5°C / min from room temperature to 850°C / min and kept warm for 20 minutes.
[0048] The acid and alkali resistance test conditions of the glass powder are 55°C, the immersion time is 60 minutes, the pH of the acid solution is 2, and the pH of the alkali solution is 10. After immersion, cleaning and drying, the glass powder is weighed to compare the quality changes before and after soaking in acid and alkali solutions.
[0049] The electrical properties of the gold film are measured by a four-probe resistance meter. In the present invention, square resistance represents the resistance between two opposite sides of a square thin film conductive material.
[0050] The bonding strength between the gold electrode and the ceramic substrate is characterized by the magnitude of the tensile force. First, a pattern of a specified area is printed on the dielectric ceramic substrate, and then sintered according to the gold paste sintering process. After the gold film is sintered, a tin wire is welded on the gold film for tensile testing.
[0051] The acid resistance results of glass powder A, B and composite glass powder in this embodiment are as follows: Figure 1 , the bonding layer at the interface between glass and substrate is as follows Figure 2 , the resistance is 5mΩ / square, and the pulling force between the gold film and the substrate is 22N.
[0052] Example 2
[0053] Except for the glass formula and the glass ratio in the slurry of this embodiment which are different from those of Embodiment 1, the other slurry processing methods, sintering processes and testing methods are exactly the same.
[0054] The slurry in this embodiment contains 85wt% gold powder, 5wt% composite glass powder, and 10wt% organic vehicle by mass percentage.
[0055] The ratio of glass powder A to glass powder B in the composite glass powder of this embodiment is 2:1. Glass powder A includes the following components in weight percentage: 10.0% P2O5, 25.0% SiO2, 25.0% B2O3, 4.0% Al2O3, 18.0% ZnO, 8.0% Na2O, 5.0% NaF, 3.0% CaO, 1.0% CuO, 2.0% Sb2O3, 3.0% ZrO2. Glass powder B includes the following components in weight percentage: 17.0% Bi2O3, 45.0% SiO2, 18.0% B2O3, 15.0% Al2O3, 3.0% K2O, 2.0% CuO.
[0056] The acid resistance results of glass powder A, B and composite glass powder in this embodiment are as follows: Figure 1 , the bonding layer at the interface between glass and substrate is as follows Figure 2 , the resistance is 7mΩ / square, and the pulling force between the gold film and the substrate is 20N.
[0057] Example 3
[0058] Except for the glass formula and the glass ratio in the slurry of this embodiment which are different from those of Embodiment 1, the other slurry processing methods, sintering processes and testing methods are exactly the same.
[0059] The slurry in this embodiment contains 85 wt % of gold powder, 3 wt % of glass powder, and 12 wt % of organic vehicle by mass percentage.
[0060] The glass powder A and glass powder B in the composite glass powder of this embodiment are 2:1, and the glass powder A includes the following components in weight percentage: 5.0% P2O5, 22.0% SiO2, 30.0% B2O3, 4.0% Al2O3, 18.0% ZnO, 8.0% Na2O, 5.0% CaO, 1.0% CuO, 1.0% Sb2O3, 1.0% ZrO2, 4.0% NaF. The glass powder B includes the following components in weight percentage: 20.0% Bi2O3, 40.0% SiO2, 20.0% B2O3, 10.0% Al2O3, 8.0% K2O, 2.0% CuO.
[0061] The acid resistance results of glass powder A, B and composite glass powder in this embodiment are as follows: Figure 1 , the bonding layer at the interface between glass and substrate is as follows Figure 2 , the resistance is 10mΩ / square, and the pulling force between the gold film and the substrate is 18N.
[0062] Example 4
[0063] Except for the glass formula and the glass ratio in the slurry of this embodiment which are different from those of Embodiment 1, the other slurry processing methods, sintering processes and testing methods are exactly the same.
[0064] The slurry in this embodiment contains 82 wt % of gold powder, 3 wt % of glass powder, and 15 wt % of organic vehicle by mass percentage.
[0065] The glass powder A and glass powder B in the composite glass powder of this embodiment are 2:1, and the glass powder A includes the following components in weight percentage: 7.0% P2O5, 20.0% SiO2, 27.0% B2O3, 2.0% Al2O3, 20.0% ZnO, 5.0% Na2O, 8.0% CaO, 2.0% CuO, 1.0% Sb2O3, 1.0% ZrO2, 7.0% NaF. The glass powder B includes the following components in weight percentage: 15.0% Bi2O3, 48.0% SiO2, 15.0% B2O3, 7.0% Al2O3, 10.0% K2O, 5.0% CuO.
[0066] The acid resistance results of glass powder A, B and composite glass powder in this embodiment are as follows: Figure 1 , the bonding layer at the interface between glass and substrate is as follows Figure 2 , the resistance is 10mΩ / square, and the pulling force between the gold film and the substrate is 15N.
[0067] Comparative Example 1
[0068] Except for the glass formula of this embodiment which is different from that of Embodiment 1, the other slurry formulas, slurry processing methods, sintering processes and testing methods are exactly the same.
[0069] The glass powder A and glass powder B in the composite glass powder of this embodiment are 2:1, and the glass powder A includes the following components in weight percentage: 25.0% SiO2, 40.0% B2O3, 4.0% Al2O3, 16.0% ZnO, 8.0% Na2O, 3.0% CaO, 2.0% CuO, 1.0% Sb2O3, 1.0% ZrO2. The glass powder B includes the following components in weight percentage: 10.0% Bi2O3, 55.0% SiO2, 15.0% B2O3, 15.0% Al2O3, 5.0% K2O.
[0070] The acid resistance results of glass powder A, B and composite glass powder in this embodiment are as follows: Figure 1 , the bonding layer at the interface between glass and substrate is as follows Figure 2 , the resistance is 50mΩ / square, and the pulling force between the gold film and the substrate is 8N.
[0071] Comparative Example 2
[0072] Except for the glass formula of this embodiment which is different from that of Embodiment 1, the other slurry formulas, slurry processing methods, sintering processes and testing methods are exactly the same.
[0073] In the composite glass powder of this embodiment, the ratio of glass powder A to glass powder B is 2:1, and glass powder A includes the following components in weight percentage: 2.0% P2O5, 25.0% SiO2, 40.0% B2O3, 4.0% Al2O3, 16.0% ZnO, 8.0% Na2O, 3.0% CaO, 2.0% ZrO2. Glass powder B includes the following components in weight percentage: 25.0% Bi2O3, 55.0% SiO2, 10.0% B2O3, 5.0% Al2O3, 5.0% K2O.
[0074] The acid resistance results of glass powder A, B and composite glass powder in this embodiment are as follows: Figure 1 , the bonding layer at the interface between glass and substrate is as follows Figure 2 , the resistance is 40mΩ / square, and the pulling force between the gold film and the substrate is 5N.
[0075] The glass formulas of glass A and glass B in the above Examples 1 to 4 and Comparative Examples 1 to 2 are shown in Table 1.
[0076] The experimental results of the composite glass powders of Examples 1 to 4 and Comparative Examples 1 to 2 are shown in Table 2. Table 1 Table 2 Composite glass powder Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Comparative Example 2 Tf(℃) 730 730 700 695 780 850 Wetting angle (°) 40 35 30 15 60 80 HT(℃) 840 840 810 800 870 950
[0077] In summary, the present invention provides a composite glass powder and a preparation method and application thereof, which is applied in gold paste for aluminum oxide and aluminum nitride substrates to form a bonding layer at the interface, thereby improving the bonding strength of the electrode.
[0078] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. By referring to the embodiments of the present invention, those skilled in the art can make various modifications to these embodiments without making creative work. Therefore, improvements and modifications made by those skilled in the art without departing from the principles of the present invention should be within the protection scope of the present invention.
Claims
1. A glass powder for conductive gold paste, characterized in that: The glass powder is a composite glass powder comprising glass powder A and glass powder B, and the ratio thereof is (1-3):
1.
2. The glass powder A according to claim 1, characterized in that: Glass powder A includes the following components calculated by mole percentage: 2-10.0% P2O5, 20-30.0% SiO2, 20-40.0% B2O3, 2-10.0% Al2O3, 10-20.0% ZnO, 0~20.0% Na2O, 0~10.0% NaF, 0~10.0% CaO, 0~5.0% M, wherein M is two or three of CuO, Sb2O3, and ZrO2.
3. The glass powder B according to claim 1, characterized in that: The glass powder B comprises the following components calculated by mole percentage: 15-30% Bi2O3, 30-50.0% SiO2, 10.0-25.0% B2O3, 5.0-15.0% Al2O3, 0-10.0% K2O, 0~5.0%CuO.
4. The glass powder according to claim 1, characterized in that: The D50 of glass powder A and B is less than 3 microns, the D100 is less than 15 microns, and the expansion coefficient is 6-8.5 ppm / °C. The spheroidization temperature of glass powder A is 700-750°C. The spheroidization temperature of glass powder B is 600-700°C.
5. Preparation of the glass powder according to claims 1 to 3, characterized in that: The following steps are involved: S1. Weigh glass raw materials, put them into a mortar and mix them for 10 to 15 minutes, then put them into a platinum crucible and melt them at 1250-1350°C for 60 to 90 minutes. Then pour the molten glass into a double-roll mill for quenching to make the molten glass into glass sheets. S2. Use a planetary ball mill to coarsely grind the glass flakes prepared in step S1 for 40-60 minutes and then sieve, and then finely grind for 70-120 minutes, dry and sieve to obtain glass powder. During the fine grinding process, water or alcohol is added as a ball grinding medium, and the mass ratio of water to glass powder is 1: (1.5-3.0).
6. The use of a glass powder as claimed in claim 1, characterized in that: The glass powder is used as a bonding phase and sintering aid of the conductive gold paste. The conductive gold paste is prepared by mixing 80-85% of gold powder, 2-7% of glass powder, and 10-15% of an organic carrier in terms of mass percentage.
7. The gold powder according to claim 6, characterized in that: The gold powder is a mixture of spherical or quasi-spherical gold powder A and gold powder B in a ratio of (1-3):
1. The D50 of gold powder A is 1-5 microns and the specific surface area is 8-12 g / cm 3 . Gold powder B has a D50 of 7 to 10 microns and a specific surface area of 3 to 7 g / cm 3 .
8. The method for preparing the gold paste as claimed in claim 6 comprises the following steps: S21, weighing the solvent and the resin, uniformly dissolving the resin in the solvent at 80-90° C., and fully stirring to form a uniform organic carrier. S22, weigh the organic carrier, glass powder A, glass powder B, gold powder and gold powder B prepared in step S21 in proportion and stir to form a uniform slurry. Use a three-roll mill to fully grind the slurry to finally prepare a gold paste that meets the performance requirements.
9. The use of the gold paste according to claim 8, characterized in that: The slurry is printed on the surface of an aluminum oxide or aluminum nitride substrate, and then dried and sintered in sequence to obtain a printed electrode. The drying temperature is 120-150°C for 10-20 minutes; the sintering process is: first, in an air atmosphere, the temperature is increased to 600°C at a heating rate of 10-15°C / min, and then the temperature is kept for 30 minutes to 60 minutes, and then in an air atmosphere, the temperature is increased to 800-900°C at a heating rate of 10-15°C / min, and then the temperature is kept for 2-3 hours; the printed electrode consists of a gold film and a substrate, and the gold film has no warping or cracking; the average square resistance of the gold film is 4.5-15.3mΩ / square, and the tension between the gold film and the substrate is 10-25N.
10. The use of the glass powder according to claim 1, characterized in that: The application scenarios of this glass powder are not limited to gold paste, but can achieve high-strength interface bonding in the fields of copper paste, nickel paste, silver paste and ceramic sealing.
Citation Information
Patent Citations
Doped slurry used for N-type solar cell metallization
CN104835552A
Thick-film silver-platinum resistance paste based on stainless steel base material and preparation method thereof
CN110931145A
Double-component high-contact glass powder for solar front silver paste
CN111268915A
Pore-filling slurry and pore-filling method for low-temperature co-fired ceramic system
CN117564263A
Gold conductive paste
JP1985025289A
Cited By
Gold electrode conductive paste and electronic circuit
CN119724680A
A gold electrode conductive paste and an electronic circuit
CN119724680B
